2003
DOI: 10.1002/dmrr.393
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy for the treatment of diabetic dyslipidemia

Abstract: The increasing prevalence of type 2 diabetes is a major problem for healthcare providers globally, since it is associated with serious microvascular and macrovascular complications. Although microvascular complications can be largely reduced with strict glycemic control, prevention of macrovascular disease involves a multifaceted approach that addresses all major risk factors, including dyslipidemia, hypertension, and insulin insensitivity. In particular, the treatment of diabetic dyslipidemia is a major chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…7,9,33 Several studies have also shown that LDL-C lowering with statins in patients with DM significantly reduced the risk of cardiovascular events. 25,34 The Heart Protection Study demonstrated that, following treatment with simvastatin, the patients with diabetes without a previous history of CHD or high cholesterol benefited by a ORIGINAL ARTICLE Table 4. Baseline and percent change in lipid measures and high-sensitivity C-reactive protein in CHD or CHD risk- one-third reduction in the incidence of coronary events.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,33 Several studies have also shown that LDL-C lowering with statins in patients with DM significantly reduced the risk of cardiovascular events. 25,34 The Heart Protection Study demonstrated that, following treatment with simvastatin, the patients with diabetes without a previous history of CHD or high cholesterol benefited by a ORIGINAL ARTICLE Table 4. Baseline and percent change in lipid measures and high-sensitivity C-reactive protein in CHD or CHD risk- one-third reduction in the incidence of coronary events.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary targets of therapy such as hypertriglyceridemia, low high density lipoprotein(HDL) cholesterol and high LDL+very low LDL and inflammation are also identified for treatment by the NCEP panel causing a further increase in the use of lipid lowering agents. The role of lipids and inflammation, in vascular disease in diabetes has been established, which would further enhance the use of statins and combination among patients with diabetic dyslipidemia [49,50]. In a randomized,controlled intervention trial, among 71patients (Intervention group) and 73 patients(Control group) of acute myocardial infarction(AMI), who were administered coenzyme Q10(120mg/day) or B vitamins for one year, half of the patients(n=36 vs 31) in both groups, received lovastatin(10-20mg/day) [51].…”
Section: Mediterranean Dietmentioning
confidence: 99%
“…In the UK, more than 70% of individuals with Type 2 diabetes have plasma cholesterol levels higher than those recommended in guidelines for the management of patients at risk of cardiovascular disease [5]. The increased cardiovascular risk in subjects with Type 2 diabetes is attributed to the clustering of atherogenic risk factors, including hypertension, abdominal obesity and dyslipidaemia [6]. Dyslipidaemia in diabetes is characterized by elevated levels of apolipoprotein (apo)B and triglycerides (TG), small dense low‐density lipoprotein cholesterol (LDL‐C), and low levels of high‐density lipoprotein cholesterol (HDL‐C), specifically the atheroprotective HDL‐2 subtype [7].…”
Section: Introductionmentioning
confidence: 99%